2016
DOI: 10.1108/jmhtep-01-2016-0006
|View full text |Cite
|
Sign up to set email alerts
|

Developing involvement during a programme of recovery research

Abstract: 2 Abstract PurposeTo consider the process of working with a Lived Experience Advisory Group (LEAP) and its outcomes in REFOCUS, a large 5 year programme of recovery research. DesignNarrative reflections on the experience of working with LEAP were collected from five members and the Chair of LEAP, two REFOCUS researchers and the Principal Investigator (PI). These were synthesised to show both the process and outcomes of LEAP involvement in REFOCUS, and how involvement evolved organically over time. FindingsIndi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 8 publications
(14 reference statements)
0
13
0
Order By: Relevance
“…Although they broadly move from lower (Approach 1) to higher (Approach 4) involvement, they cannot be simplistically allocated to a level of involvement. For example, in RECOLLECT the academic researchers included people with a range of lived experience, several study applicants self-identified as having lived experience, and the PI has published and been influenced by PPI impact assessment studies [ 60 , 61 ]. Similarly, the PPI group had members with a range of research experience.…”
Section: Discussionmentioning
confidence: 99%
“…Although they broadly move from lower (Approach 1) to higher (Approach 4) involvement, they cannot be simplistically allocated to a level of involvement. For example, in RECOLLECT the academic researchers included people with a range of lived experience, several study applicants self-identified as having lived experience, and the PI has published and been influenced by PPI impact assessment studies [ 60 , 61 ]. Similarly, the PPI group had members with a range of research experience.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the REFOCUS project [ 55 , 56 ], and consistent with the commitment to co-design [ 10 , 11 ], PULSAR is also supported by LEAP, an advisory group comprising people with either lived experience of mental illness or with experience of caring for someone with mental illness. LEAP was established at the commencement of the PULSAR project and continues to meet during the trial.…”
Section: Methodsmentioning
confidence: 99%
“…This service-user led study significantly adds to the evidence base of this topic by acknowledging that self-harm recovery is multidimensional, subjective, and not entirely dependent on behavioral cessation. This is contrary to clinical recovery definitions in mainstream psychiatric discourse which still predicate mental illness recovery on the basis of the individual returning to "pre-morbid functioning" (van Eck et al, 2018;Leamy et al, 2011;Roosenschoon et al, 2019;Slade et al, 2016). This arises from the biomedical model's leaning toward symptom eradication, which inherently lends itself to a cessation model of recovery.…”
Section: Discussionmentioning
confidence: 84%